Sex-Specific Causes and Consequences of White Matter Damage in a Middle-Aged Cohort - Bonberg, Nadine; Wulms, Niklas; Dehghan-Nayyeri, Mahboobeh; Berger, Klaus; Minnerup, Heike (Frontiers in Aging Neuroscience, 2022)
Objective: To evaluate potential sex-specific effects of multiple cardiovascular risk factors on white matter pathology in normal ageing men and women, as well as potential sex-differences in the association of white matter pathology and cognitive functions. Methods: We analyzed cross-sectional data of 581 participants (median age: 53 years, 54% women) of the population-based cohort of the BiDirect Study who completed clinical examinations, five neuropsychological tests, and an 3T-MRI examination. White matter pathology was determined by the extent of white matter hyperintensities (WMH) on FLAIR images as well as the magnitude of global fractional anisotropy (FA) based on diffusion tensor imaging. Main effects, interaction as well as sex-stratified generalized linear regression models were used to evaluate the moderation effect of hypertension, diabetes mellitus, smoking, and obesity with sex on WMH and FA, respectively. Associations of imaging markers with cognitive test results were determined with linear regression models. Results: Hypertension showed stronger associations with more extensive WMH and less FA in women compared to men. Current smoking was associated with more severe WMH in women only. Adjusted for age and education, WMH were not significantly associated with cognitive tests, but higher FA was associated with better performance in motor function in both sexes and with executive functions in men, even after adjustment for cardiovascular risk factors. Conclusion: We observed a stronger association of hypertension and smoking with white matter damage in women, suggesting a higher susceptibility for vascular pathology in women. However, there was no association of WMH with cognition, and FA was associated with executive function tests only in men, suggesting a higher cognitive reserve in women.